Industrial survey of ISO surface texture parameters. (November 2017) - Todhunter, L.D.; Leach, R.K.; Lawes, S.D.A.; Blateyron, F.
Abstract: Results of an international survey are presented, detailing the use of surface texture parameters in industry. The survey received 179 responses from a total of 34 countries, revealing the use of a variety of parameters from ISO 4287, ISO 12085, ISO 13565-2/3 and ISO 25178-2. The survey responses show an increase in the number of users of profile parameters, and an increase in the range of surface texture parameters used, compared to the results from a similar survey in 1999, as well as a significant uptake of the new areal surface texture parameters. Individual sector usage is also discussed.